Автоматизований переклад з української мови на українську жестову мову: алгоритмічна реалізація - Крак, Ю.В.; Бармак, О.В.; Романишин, С.О.; Ізотов, А.В. (Проблеми програмування, 2014)
Запропоновано алгоритмічну реалізацію інформаційної технології для перекладу з української мови на жестову мову. Побудовані інфологічні моделі словників української та жестової мов, пов’язані узагальнені граматичні конструкції для забезпечення автоматизованого перекладу. Наведені експериментальні результати для перевірки ефективності запропонованої інформаційної технології. The article describes the algorithmic implementation of information technology for translation from Ukrainian into sign language. Infological model of Ukrainian and sign language dictionary, related generalized grammatical constructions for automatic translation were build. Analyzing the set of Ukrainian sentences and corresponding gesture sentences grammatical constructions for translation were built. Grammatical constructions contain parameters of word inflections for sentences. The experimental results to verify the effectiveness of the proposed information technology are given.